Encouraging Residents to Save Energy by Using Smart Transportation: Incorporating the Propensity to Save Energy into the UTAUT Model - Bożena Gajdzik; Marcin Awdziej; Magdalena Jaciow; Ilona Lipowska; Marcin Lipowski; Grzegorz Szojda; Jolanta Tkaczyk; Radosław Wolniak; Robert Wolny; Wieslaw Wes Grebski (Energies)
The rapid urbanization and technological advancements of the recent decades have increased the need for efficient and sustainable transportation solutions. This study examines the acceptance of smart transportation systems (STSs) among residents in Polish cities and explores the impact of these systems on energy-saving behaviors. Using the extended Unified Theory of Acceptance and Use of Technology (UTAUT2) model, which includes the propensity to save energy, this research seeks to understand the determinants of STS adoption. The primary research was conducted using Computer-Assisted Web Interviewing (CAWI). The sample was controlled for gender and place of residence. A sample of 471 individuals meeting the criteria of living in a city with over 200,000 residents and using smart transportation solutions in Poland were selected from the research panel. SmartPLS 4 software was used to analyze the collected data. The findings reveal that the propensity to save energy significantly influences perceived usefulness, ease of use, social influence, and hedonic motivation toward STSs. Perceived usefulness and ease of use were found to be strong predictors of the intention to use STSs, while perceived costs had a negative impact on it. This study also identified the moderating role of personal innovativeness in mitigating cost concerns. These insights underscore the importance of emphasizing energy conservation benefits and user-friendly features in promoting the use of STSs. This study concludes that aligning technological innovations with user motivations for energy conservation can enhance the adoption of sustainable transportation solutions, contributing to smarter and more sustainable urban environments.